Biogas production from food wastes: A review on recent developments and future perspectives. (September 2019) - Mirmohamadsadeghi, Safoora; Karimi, Keikhosro; Tabatabaei, Meisam; Aghbashlo, Mortaza
Abstract: Food wastes have a high biomethane production potential because of their high organic matter contents. This review paper presents an overview on the fundamentals of anaerobic digestion (AD) of food wastes. The most important influential parameters on the biomethane production, including feedstock characteristics (nutrient contents, particle size, and inhibitory compounds) and process parameters (process configuration, pH, temperature, retention time, organic loading rate, agitation, hydrogen concentration, moisture content, and inoculum), are discussed in full. Moreover, recent developments aimed at improving the AD of food wastes are classified and discussed as operational parameters optimization, additives application, digestate recirculation, frequent feeding, and feedstock pretreatment. Finally, future challenges and prospects of biogas production from food wastes are presented. Highlights: Food wastes are among the most available types of wastes worldwide. They have high organic matter contents and high biomethane production potential. The fundamentals of anaerobic digestion of food wastes are presented. Recent developments, future challenges, and prospects are classified and discussed.